2000
DOI: 10.5194/aab-43-213-2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetische Analyse der kongenitalen Hypotrichose mit Anodontie beim Rind

Abstract: Abstract. Title of the paper: Genetic analysis of congenital hypotrichosis with anodontia in cattle In three male German Holstein calves, black and white spotted, congenital hypotrichosis and nearly complete anodontia was observed. The pedigree of the probands being maternal halfsibs and grandmatemal grandsons supports a monogenic, X-linked recessive inheritance. Chromosomal Xq-deletions were not detected. Similar congenital anomalies are known in tabby mice and in humans as anhidrotic ectodermal dysplasia (ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2003
2003

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…In this pedigree, a subset of the animals from a previous study is shown (Drögemüller et al 2000a). (B) Identification of deletions within the ED1 gene in affected animals.…”
Section: Pcr Amplification and Sequencing Of Ed1 Exonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this pedigree, a subset of the animals from a previous study is shown (Drögemüller et al 2000a). (B) Identification of deletions within the ED1 gene in affected animals.…”
Section: Pcr Amplification and Sequencing Of Ed1 Exonsmentioning
confidence: 99%
“…Cattle with X-linked anhidrotic ectodermal dysplasia (ED1 also called EDA or XLHED) are characterized by hypotrichosis, a reduced number of sweat glands, and tooth abnormalities such as missing incisors and missing or defective molars (Wijeratne et al 1988;Drögemüller et al 2000a;MIA000543). Anhidrotic ectodermal dysplasia is also known in human (MIM305100) and mouse.…”
mentioning
confidence: 99%
“…Recently the molecular basis of Xlinked anhidrotic ectodermal dysplasia in cattle was elucidated. The bovine ED1 gene maps to BTA Xq22-q24 [8] and the construction of a 480-kb bacterial artificial chromosome contig and sequence analysis of the coding parts of the ED1 gene revealed that a large genomic region including exon 3 of the ED1 gene is deleted in cattle with anhidrotic ectodermal dysplasia in a family of black-and-white German Holstein cattle with three affected maternal half sibs [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Obwohl sie bereits ein gesundes Bullenkalb hervorgebracht hat, ist die Halbschwester dieser Kuh mit einer Wahrscheinlichkeit von 50% ebenfalls Anlageträgerin. Bislang bekannte Fälle von Rindern mit dem beschriebenen Phänotyp der Hypotrichose und An-/Oligodontie folgten ebenfalls einer X-chromosomalen Vererbung (3,4).…”
Section: Pathomorphologische Befundeunclassified
“…Für eine Form des erblichen Hypotrichose-Anodontie-Defektes beim Rind konnte in einer Familie der Rasse Deutsche Holstein, Farbrichtung Schwarzbunt, die molekulargenetische Ursache aufgeklärt werden (5). In dieser Familie mit vier betroffenen Bullenkälbern, die eine Hypotrichose mit fast vollständiger Zahnlosigkeit zeigten, ließ sich ebenfalls ein monogen X-chromosomal rezessiver Erbgang für den Erbdefekt nachweisen und die Lage des zunächst unbekannten Gens auf dem langen Chromosomenarm des X-Chromosoms beim Rind eingrenzen (4)…”
Section: Introductionunclassified